Student satisfaction in the Arany János Support Program - Fehérvári, Anikó (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The study presents the fi rst results of the recent research about the Arany János Support Program. The Program has been an ongoing program since 2000 and it is the only education program in Hungary with such a long history. Furthermore, it provides group social mobility for different disadvantaged groups. The role of the program has been appreciated in recent years, because there are less and less chances for acquiring higher qualifi cations for lower socio-economic groups in the Hungarian education system. Our research focuses on those factors which infl uence the students’ success and effectiveness and the ways the program contributes to these factors. The article presents the fi rst results of the student survey, highlighting the differences between the subprograms and students’ satisfaction.